Coloured hearing, colour music, colour organs, and the search for perceptually meaningful correspondences between colour and sound. (June 2022) - Spence, Charles; Di Stefano, Nicola
There has long been interest in the nature of the relationship(s) between hue and pitch or, in other words, between colour and musical/pure tones, stretching back at least as far as Newton, Goethe, Helmholtz, and beyond. In this narrative historical review, we take a closer look at the motivations that have lain behind the various assertions that have been made in the literature concerning the analogies, and possible perceptual similarities, between colour and sound. During the last century, a number of experimental psychologists have also investigated the nature of the correspondence between these two primary dimensions of perceptual experience. The multitude of different crossmodal mappings that have been put forward over the centuries are summarized, and a distinction drawn between physical/structural and psychological correspondences. The latter being further sub-divided into perceptual and affective categories. Interest in physical correspondences has typically been motivated by the structural similarities (analogous mappings) between the organization of perceptible dimensions of auditory and visual experience. Emphasis has been placed both on the similarity in terms of the number of basic categories into which pitch and colour can be arranged and also on the fact that both can be conceptualized as circular dimensions. A distinction is drawn between those commentators who have argued for a dimensional alignment of pitch and hue (based on a structural mapping), and those who appear to have been motivated by the existence of specific correspondences between particular pairs of auditory and visual stimuli instead (often, as we will see, based on the idiosyncratic correspondences that have been reported by synaesthetes). Ultimately, though, the emotional-mediation account would currently appear to provide the most parsimonious account for whatever affinity the majority of people experience between musical sounds and colour.